Social disparities in survival after diagnosis with colorectal cancer: contribution of race and insurance status - Pulte, Dianne; Jansen, Lina; Brenner, Hermann (Cancer epidemiology, 2017)
Both minority race and lack of health insurance are risk factors for lower survival in colorectal cancer (CRC) but the interaction between the two factors has not been explored in detail. Methods One to 5-year survival by race/ethnic group and insurance type for patients with CRC diagnosed in 2007-13 and registered in the Surveillance Epidemiology, and End Results database were explored. Shared frailty models were computed to further explore the association between CRC specific survival and insurance status after adjustment for demographic and treatment variables. Results: Age-adjusted 5-year survival estimates were 70.4% for non-Hispanic whites (nHW), 62.7% for non-Hispanic blacks (nHB), 70.2% for Hispanics, 64.7% for Native Americans, and 73.1% for Asian/Pacific Islanders (API). Survival was greater for patients with insurance other than Medicaid for all races, but the differential in survival varied with race, with the greatest difference being seen for nHW at +25.0% and +20.2%, respectively, for Medicaid and uninsured versus other insurance. Similar results were observed for stage- and age-specific analyses, with survival being consistently higher for nHW and API compared to other groups. After confounder adjustment, hazard ratios of 1.53 and 1.50 for CRC-specific survival were observed for Medicaid and uninsured. Racial/ethnic differences remained significant only for nHB compared to nHW. Conclusions: Race/ethnic group and insurance type are partially independent factors affecting survival expectations for patients diagnosed with CRC. NHB had lower than expected survival for all insurance types.
Gesehen am 27.04.2017